Influence of maternal physical activity on infant's body composition. (14th November 2016) - Bisson, M.; Tremblay, F.; St‐Onge, O.; Robitaille, J.; Pronovost, E.; Simonyan, D.; Marc, I.
Summary: Background: Physical activity (PA) during pregnancy might contribute to reduce neonatal adiposity, a predictor of metabolic disturbances. Objective: The objective of the study was to evaluate the association between maternal PA intensity and neonatal body composition. Methods: Maternal PA measured by accelerometry and nutrition were documented during pregnancy, as well as neonatal body composition by dual‐energy X‐ray absorptiometry following delivery. Associations between PA at 17 and 36 weeks (time spent in moderate PA (MPA), vigorous PA (VPA) status and their interaction) and neonatal body composition were addressed by multivariate regression analyses. Results: From 104 women, 50 (48%) and 16 (18%) performed VPA at 17 and 36 weeks of pregnancy. Performing VPA at either time was associated with a decreased birthweight (BW), while only VPA at 17 weeks decreased neonatal adiposity (fat percentage: −2.3 ± 0.8%, p = 0.003). MPA at 36 weeks was associated with an increased lean mass (2.0 ± 0.8 g per min day −1, p = 0.012). Significant interactions were found for BW and bone mineral content (BMC). MPA at 17 weeks tended to increase BW, but not BMC, in the no VPA strata. By contrast, high levels of MPA (≥112 min d −1 ) combined with VPA at 17 weeks reduced neonatal BMC and BW compared with no VPA (BMC: −5.4 ± 2.0 g, p = 0.008, BW: −302.8 ± 83.7 g, p = 0.0003). Differences were not significant with low MPA levels. Conclusions: Exercise intensity modulates neonatal body composition. The long‐term significance of a reduced BW, adiposity and BMC with VPA requires further study.